(untitled) (Research, Society and Development, 2021)
The quality of dietary intake is related to weight gain during pregnancy, maternal wellbeing and fetal development, therefore, the present study aimed to investigate the diet quality index of high-risk pregnant women. A descriptive, quantitative cross-sectional study carried out with high-risk pregnant women, attended at Hospital das Clínicas of Federal University of Pernambuco (HCUFPE), between August and November 2020. Sampling carried out by convenience, including high-risk pregnant women eligible for research. Information on socioeconomic, demographic, clinical, obstetric and anthropometric data were collected. Dietary intake was obtained from a 24-hour food record, whose analysis resulted in the diet quality index adapted for pregnant women (IQDAG) which higher scores indicate a better dietary pattern. To statistical analysis were used Fisher’s exact, Pearson’s Qui-Square and Kruskal-Wallis tests, with a significance level of 5%. The sample was 126 high-risk pregnant women, and the average IQDAG score was 50,9±14,8. Better quality of diet was observed among pregnant women of older age, better degree of education, who have participation in the labor Market, who started gestation with adequate weight and diagnosed with Hypertensive Gestational Syndrome. Except the legume group, the adequacy of the other components was lower than 50% in most of the sample. The intake of ultra-processed foods showed an inverse correlation with IDQAD (-0,674), present in large amounts in the diet of pregnant women with the lowest scores. The IQDAG evaluation revealed an elevated consumption of ultra-processed foods, deficiency of essential nutrients such as folate, iron, fiber, omega-3, and low consumption of vegetables and fresh fruits.